A spontaneous transomental hernia: A rare cause of bowel obstruction - UPRAK, TEVFİK KIVILCIM (My University, 2023)
Internal hernias (IH) are rare situations that account for 0.5-3% of all cases of intestinal obstruction. Transomental hernia is a rare subtype, hardly diagnosed, and represents approximately only 2% of internal hernias. In 2018, a 41-year-old female patient presented to Marmara University Hospital emergency service with abdominal pain, nausea, and vomiting. Her medical history included asthma, and she had no abdominal surgery. With the preliminary diagnosis of small bowel obstruction, laparotomy was done and showed a loop of ileum was herniated through into an unusual defect of the omentum. The obstructed loop of the small intestine into the hernia site was reduced. It was seen as viable, so no resection was necessitated. We divided the greater omentum into two parts from the edge of the defect area to prevent recurrences. The patient\"s postoperative period was uneventful, and she was discharged on the second postoperative day. Small bowel strangulation is more seen in transomental hernia than in other internal hernia types. So it is related to high morbidity and mortality. Surgery should not be delayed to reduce complications.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); İş Sağlığı ve Terapisi; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Sağlık Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Safety Research; Health (social science); General Social Sciences; Public Health, Environmental and Occupational Health; Epidemiology; Health Sciences; Social Sciences & Humanities; Transomental hernia; Internal hernias; Small bowel obstruction; Omentum; Transomental hernia; Internal hernias; Small bowel obstruction; Omentum